2020
DOI: 10.1089/chi.2019.0040
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Therapy Reduces Obesity Indices in Children and Adolescents: A Systematic Review and Meta-Analysis of Randomized Clinical Trials

Abstract: Purpose: Few studies have summarized findings for the effect of metformin on obesity indices. Therefore, we aimed to conduct a systematic review and meta-analysis on the effect of metformin on obesity indices among children and adolescents.Methods: Relevant articles published up to September 2018 were searched in SCOPUS, Medline, and Google Scholar using appropriate keywords. All clinical trials that examined the effect of metformin on obesity indices in children and adolescents were included.Results: Overall,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 60 publications
(263 reference statements)
0
27
0
2
Order By: Relevance
“…In this study, a significant reduction of BWs in AS with MET intervention demonstrated that oral MET administration may regulate energy metabolism in AS. Sadeghi et al have shown that MET therapy reduces BMI in adolescents and adults [40]. In addition, no significant change in food intake among diverse groups indicated that the effectiveness of MET intervention was not attributed to the differential food intake.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…In this study, a significant reduction of BWs in AS with MET intervention demonstrated that oral MET administration may regulate energy metabolism in AS. Sadeghi et al have shown that MET therapy reduces BMI in adolescents and adults [40]. In addition, no significant change in food intake among diverse groups indicated that the effectiveness of MET intervention was not attributed to the differential food intake.…”
Section: Plos Onementioning
confidence: 99%
“…A study showed a significant decrease of Akkermansia in atherosclerotic ApoE -/mice [58]. MET has been proven to improve metabolic profiles in aged obese mice partially through modulating gut Akkermansia [40]. Transplantation of extracellular vesicles of Akkermansia muciniphila improved the BW and lipid profiles of the mice [59].…”
Section: Plos Onementioning
confidence: 99%
“…A large systematic review and metaanalysis (38 RCTs; n = 2199) published in 2020 evaluated metformin therapy in children and adolescents (including those with metabolic disease, growth problems, and psychological disorders in addition to obesity and overweight). 1 Over an average of 6 months, metformin use modestly reduced BMI (weighted mean difference [WMD] = -1.07 kg/m 2 ; 95% CI, -1.43 to -0.72 kg/m 2 ) and body weight (WMD = -2.51 kg; 95% CI, -3.14 to -1.89 kg) for all participants. 1 However, the authors also performed a meta-analysis of trials involving obese or overweight youth without other comorbidities.…”
Section: Metformin Has Modest Effects On Body Weightmentioning
confidence: 98%
“…1 Over an average of 6 months, metformin use modestly reduced BMI (weighted mean difference [WMD] = -1.07 kg/m 2 ; 95% CI, -1.43 to -0.72 kg/m 2 ) and body weight (WMD = -2.51 kg; 95% CI, -3.14 to -1.89 kg) for all participants. 1 However, the authors also performed a meta-analysis of trials involving obese or overweight youth without other comorbidities. Participants in these trials ranged in age from 7 to 17 years (mean not supplied; most trials, 12-15 years), had a BMI greater than the 95th percentile for age, and took doses of metformin ranging from 1500 to 3000 mg (most trials, 1500-2000 mg/d for 24 weeks).…”
Section: Metformin Has Modest Effects On Body Weightmentioning
confidence: 98%
“…Possui propriedade de causar perda de peso, mas associada à mudança do estilo de vida. 61 A metformina está associada também com a melhora do perfil lipídico. Pode apresentar manifestações gastrointestinais importantes como efeitos colaterais, mas as formas de liberação prolongada reduziram drasticamente estes sintomas.…”
Section: Farmacoterapiaunclassified